Caracterización de la oferta comercializada bajo la etiqueta de turismo responsable en España - González Reverté, Francesc (Boletín de la Asociación de Geógrafos Españoles, 2015)
This paper provides an empirical analysis of the current Spanish fair tourism supply. The fieldwork consisted in analyzing fair tourism travel catalogues from 14 major Spanish distributors. The characterization of the Spanish fair tourism supply is established through the analysis of the journey structure and price, the leisure practices performed by tourists during their stay and the ethical components and social responsibility associated with the travel providers. The main result is the establishment of a typology of fair tourism trips according to their formal characteristics and the role that tourism and leisure practices have in its implementation. © 2018 Udmurt State University. All rights reserved. info:eu-repo/semantics/publishedVersion